Heterotopic Gastric Mucosa in the Common Bile Duct With Cholangiocarcinoma. (December 2018) - Kim, Yeseul; Jung, Min Jung; Shin, Su-Jin
Gastric heterotopia within the biliary system is extremely rare. Moreover, the combination of gastric heterotopia in the bile duct with cholangiocarcinoma has not been reported. We describe a case of heterotopic gastric mucosa in the common bile duct with cholangiocarcinoma. An 80-year-old male was admitted with abdominal pain. Abdominal computed tomography revealed wall thickening from the hilar duct to the distal common bile duct. Biopsy from the distal bile duct showed only benign gastric foveolar-type epithelium and fundic glands. Although the diagnosis of the biopsy was benign, malignancy was strongly suspected from the radiologic findings, and excision of the bile ducts was performed. Microscopically, the resected specimen showed poorly formed malignant glands and gastric heterotopia also identified in the common bile duct. Three months later, the patient's state worsened due to recurrence, and he died. To our knowledge, this is the first report of gastric heterotopia in the bile duct accompanying cholangiocarcinoma.